2012
DOI: 10.1227/neu.0b013e31825927d6
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Outflow in a Large-Animal Model of Posttraumatic Syringomyelia

Abstract: In this model of posttraumatic syringomyelia, fluid outflow occurred in a diffuse manner into the surrounding extracellular space and toward the central canal and perivascular spaces. Fluid outflow may be an important consideration in the pathogenesis of syringomyelia and the development of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In fact, CSF flowed preferentially into the syrinx, ahead of perivascular flow into the rostral portions of the SC (Brodbelt et al, 2003a). A more recent animal study from the same group demonstrated extra-canalicular syrinx fluid egress by tracking HRP reaction product in adjacent grey and white matter and around the central canal and perivascular spaces (Wong et al, 2012).…”
Section: Where Does Syrinx Fluid Originate?mentioning
confidence: 94%
See 2 more Smart Citations
“…In fact, CSF flowed preferentially into the syrinx, ahead of perivascular flow into the rostral portions of the SC (Brodbelt et al, 2003a). A more recent animal study from the same group demonstrated extra-canalicular syrinx fluid egress by tracking HRP reaction product in adjacent grey and white matter and around the central canal and perivascular spaces (Wong et al, 2012).…”
Section: Where Does Syrinx Fluid Originate?mentioning
confidence: 94%
“…The ISF and nerve cells form a poroelastic material 3 . Tracer studies in animals indicate that the grey and white matter permit bulk ISF flow (e.g., Wong et al, 2012), which may be anisotropic (Saadoun and Papadopoulos, 2010). However, the dominant mechanism by which excess fluid is eliminated from the cord remains obscure.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of sheep is appropriate because much is known of its CSF physiology [7-10] . Additionally, kaolin has been used to induce hydrocephalus in fetal sheep [11,12] and has also been used to create syringomyelia in adult sheep [13]. As part of this study, the relationship between shunt success/failure with the clinical status was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…McLaurin and associates firstly described using kaolin injection into the cisterna magna consistently resulted in the development of chronic obstructive hydrocephalus in experimental animals 21 . Then a series of experimental SM models induced by kaolin injection into spinal cord and subarachnoid space have been reported [22][23][24][25][26][27][28][29] . Inflammatory…”
Section: Discussionmentioning
confidence: 99%